2015
DOI: 10.1186/s12889-015-1504-0
|View full text |Cite
|
Sign up to set email alerts
|

“In a situation of rescuing life”: meanings given to diabetes symptoms and care-seeking practices among adults in Southeastern Tanzania: a qualitative inquiry

Abstract: BackgroundDiabetes mellitus is an emerging public health problem in Tanzania. For the community and the health system to respond adequately to this problem, it is important that we understand the meanings given to its symptoms, and the care-seeking practices of individuals.MethodsTo explore collective views on the meanings given to diabetes symptoms, we conducted nine focus group discussions with adult diabetes patients and members of the general community. To gain a better understanding of how the meanings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Findings relating to how Participants recognised and interpreted their type 2 diabetes were reported in most papers included in the review [ 8 10 , 18 34 ]. A recurring observation was that the symptoms of diabetes were often not recognised by those experiencing them, and healthcare professionals tended to be the first to respond to signs of the disease [ 8 , 21 , 26 , 27 , 30 , 33 ]. For example, an informant in Hjelm and Munfunda’s study of health beliefs amongst Zimbabweans with diabetes described:…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Findings relating to how Participants recognised and interpreted their type 2 diabetes were reported in most papers included in the review [ 8 10 , 18 34 ]. A recurring observation was that the symptoms of diabetes were often not recognised by those experiencing them, and healthcare professionals tended to be the first to respond to signs of the disease [ 8 , 21 , 26 , 27 , 30 , 33 ]. For example, an informant in Hjelm and Munfunda’s study of health beliefs amongst Zimbabweans with diabetes described:…”
Section: Resultsmentioning
confidence: 99%
“…The chronic nature of diabetes was also a source of contention for study participants [ 10 , 19 , 20 , 24 , 26 , 30 ]. The majority of studies found that people with diabetes understood that diabetes was a chronic condition for which there was no cure, as this Tanzanian woman exemplifies [ 10 , 18 , 21 , 24 , 26 , 27 , 31 , 32 ]:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations